Evaluation of the Effectiveness of Campus Visits on Higher Education Enrollment - Raut, Nurmalasari (Journal of Educational Research and Policies, 2024)
Colleges and universities throughout the United States continually strive to meet the expectations and needs of their students in an effort to increase enrollment and retention numbers. As one of the most utilized recruitment efforts performed, some have questioned the necessity and benefits of campus visits and tours. Over the years, research has been conducted to determine the effectiveness and success of campus visits throughout numerous colleges and universities. In addition, in recent years, many colleges have incorporated the use of advanced technologies and capabilities that have allowed the development of technology-based campus visits and tours. As evidenced by numerous studies, and in comparison to other enrollment and recruitment efforts, campus visits continue to be one of the most advantageous and beneficial recruitment efforts to a college campus. This paper will investigate the current research as it pertains to the overall development, benefits, and advantages of college campus visits, as well as current trends being utilized by universities to increase their use of technology-based campus tours.